2014
DOI: 10.1097/igc.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Small Cell Neuroendocrine Carcinoma of the Uterine Cervix: An Institutional Experience

Abstract: International Federation of Gynecology and Obstetrics stage, age at diagnosis, and deep stromal invasion were important prognostic factors for CSS in patients with SNEC. Adjuvant chemotherapy may provide survival benefits in surgically treated patients with early-stage SNEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…These results must be interpreted cautiously given the low number of patients treated, but those are consistent with several reports, including a large database of 290 patients treated from 1977 to 2003, reporting that age, FIGO stage, tumor size, and LVI were prognostic factors. 1,19,25,26 The very high incidence of metastatic events encourages the development of novel systemic agents in order to improve patients' outcome, and based on a more thorough molecular characterization of disease.…”
Section: Discussionmentioning
confidence: 99%
“…These results must be interpreted cautiously given the low number of patients treated, but those are consistent with several reports, including a large database of 290 patients treated from 1977 to 2003, reporting that age, FIGO stage, tumor size, and LVI were prognostic factors. 1,19,25,26 The very high incidence of metastatic events encourages the development of novel systemic agents in order to improve patients' outcome, and based on a more thorough molecular characterization of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with squamous cell carcinoma (SCC) or adenocarcinoma (ADC) of the cervix, SCNEC is more likely to be an aggressive type that develops distant metastases, even in its early stages [2]. However, past studies have shown disagreement in the 5-year overall survival (OS) rate of SCNEC.…”
Section: Introductionmentioning
confidence: 96%
“…In addition to FIGO stage [6,7], several potential prognostic factors [2,[8][9][10][11][12][13][14] including age, tumor size, lymphovascular space involvement (LVSI), lymph node metastasis (LNM), depth of stromal invasion (DSI), parametrial involvement (PI), and treatment modality have been shown to influence survival, though not in all studies. For example, Lee et al [15] reported that in patients with stage IB-IIA SCNEC, neoadjuvant chemotherapy tended to improve 5-year survival.…”
Section: Introductionmentioning
confidence: 99%
“…Given its efficacy, it is believed that platinum-based chemotherapy has the capacity to improve overall survival or progression-free survival and should be used to treat NECUC patients including patients even with an early-stage disease. [23,24] Complying with this viewpoint, Zivanovic et al [25] demonstrated that platinum-based chemotherapy significantly increased 3-year distant recurrence-free survival rate for the stage IA1-IB2 patients of SCCC. Regimens containing cisplatin and etoposide have been considered to have a survival advantage over other therapeutic combinations in either small cell lung cancer (SCLC) [26,27] or SCCC.…”
Section: Discussionmentioning
confidence: 99%